Cloning of Deleted Sequences (CODE): A Genomic Subtraction Method for Enriching and Cloning Deleted Sequences. (October 2001) - Li, J.; Wang, F.; Kashuba, V.; Wahlestedt, C.; Zabarovsky, E.R.
The deletion of specific genomic sequences is believed to influence the pathogenesis of certain diseases such as cancer. Identification of these sequences could provide novel therapeutic avenues for the treatment of disease. Here, we describe a simple and robust method called cloning of deleted sequences (CODE), which allows the selective cloning of deleted sequences from complex human genomes. Briefly, genomic DNA from two sources (human normal and tumor samples) was digested with restriction enzymes (e.g., Bam HI, Bgl II, and Bcl I), then ligated to special linkers, and amplified by PCR. Tester (normal) DNA was amplified using a biotinylated primer and dNTPs. Driver (tumor) DNA was amplified using a non-biotinylated primer, but with dUTP instead of dTTP. After denaturation and hybridization, all the driver DNA was destroyed with uracil-DNA glycosylase (UDG), and all imperfect hybrids were digested with mung bean nuclease. Sequences deleted from the driver DNA but present in the tester DNA were purified with streptavidin magnetic beads, and the cycle was repeated three more times. This procedure resulted in the rapid isolation and efficient cloning of genomic sequences homozygously deleted from the driver DNA sample, but present in the tester DNA fraction.